Literature as a Medium of Healing: A Multidisciplinary Review from Psychological, Educational, and Cultural Perspectives - Seffiani Dwi Azmi (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This article explores the role of literature as a medium of healing from psychological, educational, and cultural perspectives. Literature, traditionally valued for its aesthetic qualities, has increasingly been recognized for its thera peutic functions. Through bibliotherapy and narrative engagement, literature enables individuals to experience catharsis, manage stress, and foster resilience. In educational contexts, literary texts enhance emotional intelligence, empathy, and character development, providing preventive strategies against psychological challenges among students. Meanwhile, cultural traditions such as folklore, myths, and oral narratives serve as collective healing mechanisms that reinforce identity and restore social harmony. Using a qualitative library research method and hermeneutic-critical analysis, this study demonstrates that literature functions as a holistic healing medium that bridges personal, educational, and cultural dimensions. The findings highlight the need for greater integration of literature into psychological practice, educational curricula, and cultural preservation efforts to promote individual and communal well-being in the modern era.